LRRC4 mediates the formation of circular RNA CD44 to inhibitGBM cell proliferation - Jianbo Feng; Xing Ren; Haijuan Fu; Di Li; Xiguang Chen; Xuyu Zu; Qing Liu; Minghua Wu (Elsevier, 2021)
Mounting evidence reveals that dysregulation of circular RNAs (circRNAs) is involved in the development of glioblastoma. Leucine-rich repeat-containing 4 (LRRC4) has been shown to suppress tumors in glioblastoma. However, whether LRRC4 can regulate the formation of circRNA is not yet understood. In this study, LRRC4 was found to interact with SAM68. LRRC4 promoted the generation of circCD44 by inhibiting the binding between SAM68 and CD44 pre-mRNA. Moreover, downregulated expression of circCD44 was found in glioblastoma multiforme (GBM) tissues and GBM primary cells. Re-expression of circCD44 significantly suppressed the proliferation, colony formation, and invasion of GBM cells and inhibited tumor growth in vivo. Mechanistically, circCD44 could regulate the expression of SMAD6 via sponging miR-326 and miR-330-5p involved in the progression of GBM. Thus, the LRRC4/SAM68/circCD44/miR-326/miR-330-5p/SMAD6 signaling axis could be a potential target for GBM treatment.